The role of eastern Tethys seaway closure in the Middle Miocene Climatic Transition (ca. 14 Ma) - N. Hamon (Climate of the Past, 2013)
The Middle Miocene Climatic Transition (MMCT, approximately 14 Ma) is a key period in Cenozoic cooling and cryospheric expansion. Despite being well documented in isotopic record, the causes of the MMCT are still a matter of debate. Among various hypotheses, some authors suggested that it was due the final closure of the eastern Tethys seaway and subsequent oceanic circulation reorganisation. The aim of the present study is to quantify the impact of varying Tethys seaway depths on middle Miocene ocean and climate, in order to better understand its role in the MMCT. We present four sensitivity experiments with a fully coupled ocean-atmosphere general circulation model. Our results indicate the presence of a warm and salty water source in the northern Indian Ocean when the eastern Tethys is deep open (4000 or 1000 m), which corresponds to the Tethyan Indian Saline Water (TISW) described on the basis of isotopic studies. This water source is absent in the experiments with shallow (250 m) and closed Tethys seaway, inducing strong changes in the latitudinal density gradient and ultimately the reinforcement of the Antarctic Circumpolar Current (ACC). Moreover, when the Tethys seaway is shallow or closed, there is a westward water flow in the Gibraltar Strait that strengthens the Atlantic Meridional Overturning Circulation (AMOC) compared to the experiments with deep-open Tethys seaway. Our results therefore suggest that the shoaling and final closure of the eastern Tethys seaway played a major role in the oceanic circulation reorganisation during the middle Miocene. The results presented here provide new constraints on the timing of the Tethys seaway closure and particularly indicate that, prior to 14 Ma, a deep-open Tethys seaway should have allowed the formation of TISW. Moreover, whereas the final closure of this seaway likely played a major role in the reorganisation of oceanic circulation, we suggest that it was not the main driver of the global cooling and Antarctica ice-sheet expansion during the MMCT. Here we propose that the initiation of the MMCT was caused by an atmospheric pCO2 drawdown and that the oceanic changes due to the Tethys seaway closure amplified the response of global climate and East Antarctic Ice Sheet.